Листопад: стихотворения / Геннадий Шкляев - Шкляев Геннадий Павлович (Инвожо, 2016)
Экземпляры: СБ (20181115) / Инвентарный номер: 56699 / Цена: 60.00 / Сис.шифр: Р2 / Авт.знак: Ш 66 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Удм)6